Aedes aegypti microbiome composition covaries with the density of Wolbachia infection - Jane Pascar; Henry Middleton; Steve Dorus (Microbiome, 2023)
Abstract Background Wolbachia is a widespread bacterial endosymbiont that can inhibit vector competency when stably transinfected into the mosquito, Aedes aegypti, a primary vector of the dengue virus (DENV) and other arboviruses. Although a complete mechanistic understanding of pathogen blocking is lacking, it is likely to involve host immunity induction and resource competition between Wolbachia and DENV, both of which may be impacted by microbiome composition. The potential impact of Wolbachia transinfection on host fitness is also of importance given the widespread release of mosquitos infected with the Drosophila melanogaster strain of Wolbachia (wMel) in wild populations. Here, population-level genomic data from Ae. aegypti was surveyed to establish the relationship between the density of wMel infection and the composition of the host microbiome. Results Analysis of genomic data from 172 Ae. aegypti females across six populations resulted in an expanded and quantitatively refined, species-level characterization of the bacterial, archaeal, and fungal microbiome. This included 844 species of bacteria across 23 phyla, of which 54 species were found to be ubiquitous microbiome members across these populations. The density of wMel infection was highly variable between individuals and negatively correlated with microbiome diversity. Network analyses revealed wMel as a hub comprised solely of negative interactions with other bacterial species. This contrasted with the large and highly interconnected network of other microbiome species that may represent members of the midgut microbiome community in this population. Conclusion Our bioinformatic survey provided a species-level characterization of Ae. aegypti microbiome composition and variation. wMel load varied substantially across populations and individuals and, importantly, wMel was a major hub of a negative interactions across the microbiome. These interactions may be an inherent consequence of heightened pathogen blocking in densely infected individuals or, alternatively, may result from antagonistic Wolbachia-incompatible bacteria that could impede the efficacy of wMel as a biological control agent in future applications. The relationship between wMel infection variation and the microbiome warrants further investigation in the context of developing wMel as a multivalent control agent against other arboviruses. Video Abstract